Post‐treatment efficacy of discontinuous treatment with 300IR 5‐grass pollen sublingual tablet in adults with grass pollen‐induced allergic rhinoconjunctivitis. Issue 5 (22nd April 2013) - Didier, A.; Malling, H.‐J.; Worm, M.; Horak, F.; Sussman, G.; Melac, M.; Soulié, S.; Zeldin, R. K.
Summary: Background: Sustained efficacy over three pollen seasons of pre‐ and co‐seasonal treatment with 300IR 5‐grass pollen sublingual tablet has been demonstrated in adults with moderate‐severe grass pollen‐associated allergic rhinoconjunctivitis. Objective: To assess the efficacy of discontinuous treatment with 300IR 5‐grass pollen sublingual tablet during the post‐treatment pollen season of this long‐term study. Methods: Adults aged 18–50, sensitized to grass pollen, with a history of allergic rhinoconjunctivitis for more than two pollen seasons, and a retrospective rhinoconjunctivitis total symptom score ≥ 12 (0–18 scale), were randomized to receive Placebo or a 300IR tablet daily beginning either 4 months (4M) or 2 months (2M) prior to each pollen season and continuing for its duration for three consecutive years. They were followed over the subsequent immunotherapy‐free pollen season. Post‐treatment efficacy was evaluated using the Average Adjusted Symptom Score (AAdSS, adjusting the Rhinoconjunctivitis Total Symptom Score for rescue medication usage) during the post‐treatment pollen period. Secondary endpoints included Average Rhinoconjunctivitis Total Symptom Score (ARTSS), Average Rescue Medication Score (ARMS), overall Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ) score and safety evaluation. Efficacy variables were analysed usingancova . Results: Overall, 435 patients contributed to the Year 4 efficacy analyses. The Least‐Squares (LS) mean differences (95% confidence interval) in AAdSS between active treatment and Placebo over the fourth pollen period were −1.14 (−2.03; −0.26) ( P = 0.0114) and −1.43 (−2.32; −0.53) ( P = 0.0019) in the (4M) and (2M) groups, corresponding to −22.9% and −28.5% relative LS mean differences (vs. Placebo) respectively. The active groups also showed statistically significant differences compared to Placebo in ARTSS, ARMS and overall RQLQ score. No safety risk was identified during the post‐treatment period. Conclusions and Clinical Relevance: Pre‐ and co‐seasonal treatment with 300IR 5‐grass pollen sublingual tablet administered discontinuously for three consecutive years is efficacious post‐treatment, safe and well tolerated. Benefits of treatment were meaningful to patients.